Experimental study and modeling of bond of carbon-fiber-reinforced polymer grids to polymer mortar at room and elevated temperatures. Issue 8 (June 2020) - Liu, Zongquan; Yue, Qingrui; Li, Rong; Chen, Xiaobing
Carbon-fiber-reinforced polymer grids encased with polymer mortar have received much attention lately as an effective technology for strengthening concrete structures. The objective of this study was to investigate the bond-slip behavior of carbon-fiber-reinforced polymer grids to polymer mortar at room and elevated temperatures. First, 20 pull-out specimens were tested at room temperature of 20°C, and the investigated parameters included the type of carbon-fiber-reinforced polymer grids, the embedment length of longitudinal bar, and the transverse bar length. Based on the experimental results, a two-branch bond-slip model at room temperature was proposed, with the characteristic bond stress and the corresponding slip determined by the regression analysis of test data. Second, 24 pull-out specimens were tested at elevated temperatures over a range of 20°C–300°C, and the investigated parameters included the type of carbon-fiber-reinforced polymer grids and the testing temperature. Based on the experimental results, a bond-slip model at elevated temperatures was further proposed by modeling the temperature-dependent reduction factors. The two proposed bond-slip models will be particularly useful in the theoretical analysis of structures with carbon-fiber-reinforced polymer grids and polymer mortar strengthening system under both room and elevated temperatures.